Effect of planting system of potato and plant density of maize on productivity of potato- hybrid maize intercropping system (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at Agronomy Research Field, Bangladesh Agricultural Research Institute, Gazipur during 2010-11 to find out the appropriate planting system of potato and plant density of maize in potatohybrid maize intercropping system for maximum yield and economic return. Ten treatments were evaluated viz., T1= Potato whole tuber single row (75 cm × 20 cm) + 125% hybrid maize (75 cm × 20 cm), T2=Potato whole tuber single row (75 cm × 20 cm) + 100% hybrid maize (75cm × 25 cm), T3= Potato whole tuber single row (75 cm × 20 cm) + 83% hybrid maize (75 cm × 30 cm), T4= Potato half tuber paired row (20 cm/ 55 cm × 20 cm) + 125% hybrid maize (75 cm × 20 cm), T5= Potato half tuber paired row (20 cm/ 55 cm × 20 cm) +100% hybrid maize (75 cm × 25 cm), T6= Potato half tuber paired row (20 cm/ 55 cm × 20 cm) + 83% hybrid maize (75 cm × 30 cm), T7= Sole potato whole tuber single row planting system (60 cm × 25 cm), T8 = Sole potato half tuber paired row (20 cm/ 55 cm × 20 cm), T9= Sole hybrid maize in normal spacing 75 cm × 25 cm (sole HM1) and T10= Sole hybrid maize (75 cm × 25 cm) sown 30 days after potato planting (sole HM2). The results revealed that sole planting of both potato and maize produced the maximum yields. In case of sole potato, potato half tuber paired row planting system was better than potato whole tuber single row planting system. On the other hand, the performance of sole HM1 was better than sole HM2 in relation to growth, yield and economic performance. Over all T1 treatment ( potato whole tuber single row planting system with 125 % hybrid maize population) was the best intercropping system for getting higher yield and economic return as well as less relative crowding coefficient with better crop performance ratio.Bangladesh J. Agril. Res. 41(3): 397-409, September 2016